Chaining ＆ counter-based block cipher mode for authentication - HUANG Yu-hua1; HU Ai-qun2; WANG Jian-dong1 (Tongxin xuebao)
For raising the operation efficiency of block cipher algorithms,a fast authentication mode based on chaining ＆ counter（CCTR） was put forward;and its security was proved.Its speed was about 30% faster than that of authentication modes in common use（for example,CBC-MAC）.The dependence test results accord with the demands.The CCTR mode is complete;its degree of avalanche effect is about 0.999 3;its degree of strict avalanche criterion is 0.992 or so.The frequency test results indicate that the output generated by the CCTR mode had uniformity.The binary matrix rank,Run,spectral,non-overlapping template matching,overlapping template matching,Maurer’s universal statistical test,Lempel-Ziv compression,linear complexity,serial,approximate entropy,cumulative sums,random excursions and random excursions variant tests results fulfilled the requirements all.Therefore,the CCTR mode has good pseudo-randomness,which the security of CCTR mode is verified by way of statistical evaluation.